If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -1y)(2y + 9) = 0 Reorder the terms: (6 + -1y)(9 + 2y) = 0 Multiply (6 + -1y) * (9 + 2y) (6(9 + 2y) + -1y * (9 + 2y)) = 0 ((9 * 6 + 2y * 6) + -1y * (9 + 2y)) = 0 ((54 + 12y) + -1y * (9 + 2y)) = 0 (54 + 12y + (9 * -1y + 2y * -1y)) = 0 (54 + 12y + (-9y + -2y2)) = 0 Combine like terms: 12y + -9y = 3y (54 + 3y + -2y2) = 0 Solving 54 + 3y + -2y2 = 0 Solving for variable 'y'. Factor a trinomial. (6 + -1y)(9 + 2y) = 0Subproblem 1
Set the factor '(6 + -1y)' equal to zero and attempt to solve: Simplifying 6 + -1y = 0 Solving 6 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 0 + -6 -1y = 0 + -6 Combine like terms: 0 + -6 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6Subproblem 2
Set the factor '(9 + 2y)' equal to zero and attempt to solve: Simplifying 9 + 2y = 0 Solving 9 + 2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 2y = 0 + -9 2y = 0 + -9 Combine like terms: 0 + -9 = -9 2y = -9 Divide each side by '2'. y = -4.5 Simplifying y = -4.5Solution
y = {6, -4.5}
| 7(t-4)-6t=10 | | 9v-7=-43 | | 1+4u=-3+2u | | -3(x-5)+9+x=54 | | 4v-5=-33 | | -3q+8=8+4q | | (5p^2+p+8)(-7p-7)=0 | | 5x+10=-9x-17 | | 5d=-6+4d | | 2u-14=22 | | 10-4m=-5m | | 20+3=w | | 104=4x | | (5c+4)(8c-1)= | | 5x+13=5x-16 | | -18=2w-8 | | 8+25x-5x=20x+24-3x | | -46-7r=-(1+12r)-4r | | (K+3)(7k-3)=0 | | 10w=-8+9w | | 2w-9=3w | | 8.95+23.65=2 | | 10x=6x+2Whatisx | | x-[9x-(x-4)]=0 | | -16-(x-4)=6 | | 4y+15=95 | | 4(3y+7)= | | -10-4b=6 | | 7500-30000=36 | | 4z-10=3z | | 4x^2-4x-k=0 | | 7x-13=5+4x |